2005
DOI: 10.1016/j.cardiores.2004.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial contraction is 5-fold more economical in ventricular than in atrial human tissue

Abstract: These results clearly indicate that even a minor shift in MHC isoform expression has considerable impact on cardiac performance in human tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 30 publications
9
55
2
Order By: Relevance
“…We have previously shown a linear relationship between tension-cost and the ␣/␤-myosin ratio in both rat and mouse myocardium (25,36); a similar result was also reported in guinea-pig myocardium, albeit over a smaller range of ␣/␤-myosin ratio (43). Likewise, human ventricular myocardium displays a lower tension cost than human atrial myocardium that is largely explained by the difference in myosin composition (29). It should be noted that the tension-cost parameter is measured during an isometric contraction, that is, under conditions in which the cross-bridges are under high strain and developing force.…”
Section: Discussionsupporting
confidence: 75%
“…We have previously shown a linear relationship between tension-cost and the ␣/␤-myosin ratio in both rat and mouse myocardium (25,36); a similar result was also reported in guinea-pig myocardium, albeit over a smaller range of ␣/␤-myosin ratio (43). Likewise, human ventricular myocardium displays a lower tension cost than human atrial myocardium that is largely explained by the difference in myosin composition (29). It should be noted that the tension-cost parameter is measured during an isometric contraction, that is, under conditions in which the cross-bridges are under high strain and developing force.…”
Section: Discussionsupporting
confidence: 75%
“…While these observations are suggestive of an important role of ␣-MHC expression in the human myocardium, such an extension of the present results to humans is premature since the ATP turnover rates for both ␣-MHC and ␤-MHC are slower in humans and not known for certain. However, recent evidence has suggested that the rate of ATP utilization by ␤-MHC is nearly fivefold slower in the human myocardium than in the rodent (36). In light of this observation, our model would predict that expression of ␣-MHC on the order of 10% would dramatically increase the rate of force development and thus enhance dP/dt max .…”
Section: Implications Of Altered Mhc Expression On the Rate Of Rise Omentioning
confidence: 84%
“…Shifts in the relative expression of isoforms are common, and confer critical changes in the contractile strength and speed of the chamber contraction (Narolska et al, 2005a;Narolska et al, 2005b). Atrophy typically induces isoform transitions (Klein et al., 1992; Geenen et al, 1994;Tang et al, 2005), and cardiomyopathy generally leads to a loss of MyHC-α (Buttrick et al, 1991;Takahashi et al, 1992;Miyata et al, 2000;Reiser et al, 2001), at least in non-hibernators.…”
Section: Cardiac Myosin Isoform Expression In Ground Squirrelsmentioning
confidence: 99%
“…MyHC-α isoforms may contract 2-3 times faster, with generally lower force, but species-specific differences are apparent; average force can be similar between MyHC-α and MyHC-β (Sugiura et al, 1998;Alpert et al, 2002;Galler et al, 2002;Malmqvist et al, 2004;Narolska et al, 2005a;Narolska et al, 2005b). The expression of the isoforms varies by heart chamber, and by sex, age and mass of the individual (Cummins and Lambert, 1986;O'Neill et al, 1991;Reiser and Kline, 1998;Barrows et al, 2011).…”
Section: Cardiac Myosin Isoform Expression In Ground Squirrelsmentioning
confidence: 99%